Egyptian Religious Activity in Palestine and Syria during the Third and Second Millennia B.C. - Kuykendall, William Henry Frazer (1966)
Ph.D.; University Microfilms Order No. 66-7013. Microfilm $3.60; Xerography $12.60; Dissertation Abstracts 27/1 (Ann Arbor, Mich., July 1966) 157-A.